Inhibition of chemically and mechanically activated Piezo1 channels as a mechanism for ameliorating atherosclerosis with salvianolic acid B. (19th March 2022) - Pan, Xianmei; Wan, Rentao; Wang, Yuman; Liu, Silin; He, Yu; Deng, Bo; Luo, Shangfei; Chen, Yuan; Wen, Lizhen; Hong, Tianying; Xu, Han; Bian, Yifei; et al.
Abstract : Background and Purpose: Salvianolic acid B (SalB) is effective for treating cardiovascular diseases. However, the molecular mechanisms underlying its therapeutic effects remain unclear. Mechanosensitive Piezo1 channels play important roles in vascular biology, although their pharmacological properties are poorly defined. Here, we aimed to identify novel Piezo1 inhibitors and gain insights into their mechanisms of action. Experimental Approach: Intracellular Ca 2+ ions were measured in HUVECs, murine liver endothelial cells (MLECs), THP‐1 and RAW264.7 cell lines and bone marrow‐derived macrophages (BMDMs). Isometric tensions in mouse thoracic aorta were recorded. Shear‐stress assays with HUVECs were conducted. Patch‐clamp recordings with mechanical stimulation were performed with HUVECs in whole‐cell mode. Foam cell formation was induced by treating BMDMs with oxidised LDL (oxLDL). Atherosclerotic plaque assays were performed with Ldlr −/− and Piezo1 genetically depleted mice on a high‐fat diet. Key Results: Salvianolic acid B inhibited Yoda1‐induced Ca 2+ influx in HUVECs and MLECs. Similar results were observed in macrophage cell lines and BMDMs. Furthermore, we demonstrated that salvianolic acid B inhibited Yoda1‐ and mechanically activated currents. Salvianolic acid B suppressed Yoda1‐induced aortic ring relaxation and inhibited HUVECs alignment in the direction of shear stress. Additionally, Yoda1 enhanced the formation of foam cells, which was reversed by salvianolic acid B. Salvianolic acid B also inhibited formation of atherosclerotic plaques and was insensitive to Piezo1 genetic depletion. Conclusion and Implications: Our study provides novel mechanistic insights into the inhibitory role of salvianolic acid B against Piezo1 channels and improves our understanding of salvianolic acid B in preventing atherosclerotic lesions.